Mapping Contemporary Shi’a Studies: Authority, Ritual, Law, and Sectarianization - Basid, Abdul; Sulaiman, Nor Surilawana (KALAM, 2025)
This article maps recent scholarship on Shi’a Islam by asking how the field has moved beyond the language of a fixed sectarian category toward the analysis of relational mechanisms: authority, ritual, law, publicness, and sectarianization. The study uses a PRISMA-informed systematic mapping design and a DOI-verified corpus of recent publications identified from the supplied reference export, manuscript draft, and bibliographic records. Because the evidence base combines historical, theological, legal, political, ethnographic, and discourse-analytic studies, the synthesis is qualitative rather than meta-analytic. The review identifies six recurring clusters: minority publicness, sectarianization and political classification, clerical and epistemic authority, ritual memory and Ashura, legal-ethical adaptation, and Indonesian or transnational intellectual activism. Across these clusters, Shi’a Islam is increasingly studied as a mediated field of practice rather than as a single doctrinal label. The strongest evidence comes from case-based interpretation, textual analysis, and recent empirical work, while cumulative cross-regional comparison remains limited. The article argues that future Shi’a studies should connect theology, authority, ritual, law, and public recognition through transparent comparative designs. [Artikel ini memetakan perkembangan terbaru kajian tentang Islam Shi’a dengan menelaah pergeseran dari pemahaman Shi’a sebagai kategori sektarian yang statis menuju analisis mekanisme relasional: otoritas, ritual, hukum, publikitas, dan sektarianisasi. Kajian ini menggunakan desain pemetaan sistematis berbasis prinsip PRISMA dan korpus publikasi terbaru yang diverifikasi melalui DOI dari ekspor referensi, draf naskah, dan catatan bibliografis yang tersedia. Karena sumber yang dianalisis mencakup studi sejarah, teologi, hukum, politik, etnografi, dan analisis wacana, sintesis dilakukan secara kualitatif, bukan meta-analitik. Review ini menemukan enam klaster utama: publikitas minoritas, sektarianisasi dan klasifikasi politik, otoritas ulama dan otoritas epistemik, memori ritual dan Ashura, adaptasi hukum-etika, serta aktivisme intelektual Indonesia dan transnasional. Secara umum, literatur terbaru semakin memahami Islam Shi’a sebagai medan praktik yang dimediasi oleh institusi, ritual, hukum, dan pengakuan publik. Artikel ini menegaskan perlunya desain komparatif yang lebih transparan dalam kajian Shi’a masa depan.]